Molecular dissection of plasmacytoid dendritic cell activation in vivo during a viral infection - Tomasello, Elena; Naciri, Karima; Chelbi, Rabie; Bessou, Gilles; Fries, Anissa; Gressier, Elise; Abbas, Abdenour; Pollet, Emeline; Pierre, Philippe; Lawrence, Toby; Vu Manh, Thien‐Phong; Dalod, Marc (The EMBO journal, 2018)
Plasmacytoid dendritic cells (pDC) are the major source of type I interferons (IFN‐I) during viral infections, in response to triggering of endosomal Toll‐like receptors (TLRs) 7 or 9 by viral single‐stranded RNA or unmethylated CpG DNA, respectively. Synthetic ligands have been used to disentangle the underlying signaling pathways. The adaptor protein AP3 is necessary to transport molecular complexes of TLRs, synthetic CpG DNA, and MyD88 into endosomal compartments allowing interferon regulatory factor 7 (IRF7) recruitment whose phosphorylation then initiates IFN‐I production. High basal expression of IRF7 by pDC and its further enhancement by positive IFN‐I feedback signaling appear to be necessary for robust cytokine production. In contrast, we show here that in vivo during mouse cytomegalovirus (MCMV) infection pDC produce high amounts of IFN‐I downstream of the TLR9‐to‐MyD88‐to‐IRF7 signaling pathway without requiring IFN‐I positive feedback, high IRF7 expression, or AP3‐driven endosomal routing of TLRs. Hence, the current model of the molecular requirements for professional IFN‐I production by pDC, established by using synthetic TLR ligands, does not strictly apply to a physiological viral infection. Synopsis In vivo production of IFN‐I by pDC requires TLR9‐to‐MyD88‐to‐IRF7 signaling both during MCMV infection and CpG injection but IFN‐I positive feedback and AP3 function only for CpG. Hence, distinct mechanisms tune pDC responses to TLR9 triggering by synthetic ligands versus a viral infection. TLR, IFN‐I and IFN‐γ differentially contribute to pDC activation during MCMV infection, driving largely distinct gene expression programs. During MCMV infection but not CpG injection, pDC can produce IFN‐I in vivo independently of IFN‐I positive feedback and AP3‐mediated routing. IRF7 is necessary for IFN‐I production by pDC, but low amounts are sufficient to endow them with this function. Cell‐intrinsic LFA‐1 functions and hence cell‐cell interactions promote pDC cytokine production both during MCMV infection and CpG injection, but their precise nature remains unknown. Graphical Abstract Physiological settings for studying activation of interferon‐producing pDCs reveal dispensability of high basal IRF7 expression and positive IFN‐I feedback signals previously implicated based on testing with synthetic ligands.